OPTIMIZATION OF HUMAN RESOURCE MANAGEMENT TO IMPROVE THE QUALITY OF EDUCATION AT MAN 2 TULUNGAGUNG - Masduki, Masduki; Hastutik, Sri (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2024)
The principal should synergize with teachers and education personnel to improve the quality of education to determine the success of education. In this case, the subject of the study is education at MAN 2 Tulungagung. The research method is a qualitative design that uses descriptive phenomenological analysis with data analysis using the Miles, Huberman & Saldana model. The results of the study are as follows: Human resource planning, namely: planning the needs of human resources, both educators and education personnel who have a strong commitment to implementing the vision and mission to achieve the goals of the madrasah. Organizing human resources at MAN 2 Tulungagung is done by compiling job descriptions, and procuring workers. Empowerment of human resources at MAN 2 Tulungagung, namely: through coaching, supervision, training, providing motivation and reward and punishment. Evaluation of human resources at MAN 2 Tulungagung is in two forms, namely soft and hard forms. The soft form is more directed at the form of awareness and religious touch and profession. The hard form displays the evaluation of the performance report of educators and employees.